Trends of Knowledge Management in Textile Industry of Punjab - Sharma, Radha Kanwal; Kumar, Prem; Bansal, S.K (Gyan Management Journal, 2010)
Concept of knowledge isfastgaining momentum. Organizations have come to know its importance and relevance in doing business in these days of globalization and ever increasing competition. That proper management of know/edge can enhance the efficiency and quality of decision making in a company isa well known fact. In this paper an effort has been made to know the various factors responsible for increasing awareness and knowledge needs of the companies in textile industry of Punjab.